2011
DOI: 10.1016/j.bpj.2011.10.035
|View full text |Cite
|
Sign up to set email alerts
|

Active Trans-Plasma Membrane Water Cycling in Yeast Is Revealed by NMR

Abstract: Plasma membrane water transport is a crucial cellular phenomenon. Net water movement in response to an osmotic gradient changes cell volume. Steady-state exchange of water molecules, with no net flux or volume change, occurs by passive diffusion through the phospholipid bilayer and passage through membrane proteins. The hypothesis is tested that plasma membrane water exchange also correlates with ATP-driven membrane transport activity in yeast (Saccharomyces cerevisiae). Longitudinal (1)H(2)O NMR relaxation ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(124 citation statements)
references
References 38 publications
4
120
0
Order By: Relevance
“…For example, the FXR-allowed SSM version used in this study allows for a non-infinitely fast transcytolemmal exchange, modeled by the mean intracellular water molecule lifetime, τ i . This parameter has been suggested to reflect cellular metabolic activity, manifest in ATP-driven membrane transport activity in a yeast suspension study [50]. This observation was further validated in a breast DCE-MRI study [51], demonstrating that changes in τ i are not due to changes in cell sizes but rather changes in energetic metabolism-driven cell membrane water permeability.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, the FXR-allowed SSM version used in this study allows for a non-infinitely fast transcytolemmal exchange, modeled by the mean intracellular water molecule lifetime, τ i . This parameter has been suggested to reflect cellular metabolic activity, manifest in ATP-driven membrane transport activity in a yeast suspension study [50]. This observation was further validated in a breast DCE-MRI study [51], demonstrating that changes in τ i are not due to changes in cell sizes but rather changes in energetic metabolism-driven cell membrane water permeability.…”
Section: Discussionmentioning
confidence: 76%
“…This version of the SSM has been used to quantify perfusion of breast [48] and prostate cancer [49], but not in the liver. It has been suggested that τ i may reflect cellular metabolic activity [50, 51]. …”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies 12, 25, 26 have reported that τ i is inversely correlated with cell membrane ion-pump activity, a measure of mitochondrial metabolism suggesting that τ i may be a sensitive indicator of cellular energy turnover. Similarly, some studies have reported that increased metabolic activity is associated with lower τ i (median=0.16–1.03s) in regions of prostrate, 15, 16 and esophageal cancer 17 compared to normal tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Although our findings suggest that, indeed, the cell membrane is sufficient to induce a relatively low diffusivity and, in addition, the intraneuronal and intraglial peaks were well-resolved, we cannot exclude the effects of fast exchange in these two cases. The impact of exchange is expected to increase with in vivo applications because of the elevated temperature, the presence of active water and ion channels (Zhang et al, 2011), and the longer diffusion times necessary when using clinical systems. This issue may be addressed by direct measurement of the exchange rate spectrum, either via relaxation exchange spectroscopy (REXSY) (Lee et al, 1993) or via diffusion exchange spectroscopy (DEXSY) (Callaghan and Fur’o, 2004).…”
Section: Resultsmentioning
confidence: 99%